2015
DOI: 10.1302/0301-620x.97b9.35292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of extended osteochondral lesions of the talus with a free vascularised bone graft from the medial condyle of the femur

Abstract: Large osteochondral lesions (OCLs) of the shoulder of the talus cannot always be treated by traditional osteochondral autograft techniques because of their size, articular geometry and loss of an articular buttress. We hypothesised that they could be treated by transplantation of a vascularised corticoperiosteal graft from the ipsilateral medial femoral condyle. Between 2004 and 2011, we carried out a prospective study of a consecutive series of 14 patients (five women, nine men; mean age 34.8 years, 20 to 54)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…11,26 In their series of MFC flaps for talus OCLs, however, Hintermann et al demonstrated complete incorporation of the bone flap within 8-13 weeks. 13 Similar to their higher AOFAS scores, the longer time to union observed in our cohort likely reflects more severe baseline pathology among our patients. Their mean flap volume was 3.36 cm 3 compared with 10.4 cm 3 in our patients indicating significantly larger defect size; however, flap volume was not found to correlate with time to union in our cohort.…”
Section: Discussionsupporting
confidence: 55%
“…11,26 In their series of MFC flaps for talus OCLs, however, Hintermann et al demonstrated complete incorporation of the bone flap within 8-13 weeks. 13 Similar to their higher AOFAS scores, the longer time to union observed in our cohort likely reflects more severe baseline pathology among our patients. Their mean flap volume was 3.36 cm 3 compared with 10.4 cm 3 in our patients indicating significantly larger defect size; however, flap volume was not found to correlate with time to union in our cohort.…”
Section: Discussionsupporting
confidence: 55%
“… a RTS, return to sports. b References 1, 13, 17, 21, 22, 27, 28, 31, 32, 36, 39, 46, 48, 61, 63 65, 76, 85, 86, 98. c Range of means of original data.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nineteen patients, fourteen were successfully treated according to the AOFAS, resulting in a success percentage of 74% [CI 51–88%]. The second study included in this group was a transplantation method using a bone graft [ 24 ]. As the bone graft was vascularized, the authors decided not to include this study in the previously described osteochondral transplantation group.…”
Section: Resultsmentioning
confidence: 99%